Psychoeducation in the Process of Rehabilitation of People with Disability and Chronic Illness - Piotr Majewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article is a review concerning psychoeducation and ways of using it by teachers in the process of supporting the development and functioning of people with disability, chronic physical illness and mental disorders. There are presented some theoretical basis of psychoeducation as well as the areas, aims and some of the results of previous studies. Moreover, selected programs such as the Barcelona Psychoeducation Program, PEGASUS Program and Cracow Psychoeducation Program are also described.   Practical psychoeducational actions stimulate psychosocial development of people with disabilities and chronic illness. They make the rehabilitation and treatment process complete and in the case of mental disorders are an integral part of the therapy.